The Effect of the PQ4R Strategy on Academic Achievement and Reducing Cognitive Closure in the History Subject for Eleventh-Grade Middle School Students - Sabah Rahman MohammadAli; Hawzheen Mahmood Azeez (Zanco Journal of Human Sciences, 2026)
As a history teacher, the researcher found that there is a problem of poor academic achievement among students in history. To overcome this problem, he suggests the use of PQ4R strategy. In order to determine the effect of PQ4R strategy on academic achievement among eleventh grade students, this study used an experimental approach, two groups (experimental and controlled) in the research community, which is Sazani Girls High School in Erbil province center For the year (2024-2025), the basic sample of the study consisted of (77) girl students, who, two eleventh grades of literature (A, B), consisted of, randomly, grade (A) was selected to represent the experimental group Strategy (PQ4R) study history, and grade (b) represents the control group, who study history in the normal way, the experimental group (38) students and the control group (39) students After using the spss statistical tool (for social sciences, to analyze the results of the study, the statistical tools used are (Spearman, Person, Co-Collection and Cronbach, Tai test, Kai2 test and deviation criterion and arithmetic center and Jetman). The results showed that the experimental group's academic achievement in history has changed significantly, their level has increased, this is due to the impact of the strategy (PQ4R) implemented on the experimental group.